Teleworking in times of a pandemic: An applied study of industrial companies - Becerra-Astudillo, Laura; Vargas-Díaz, Belén; Molina, Carlos; Serrano-Malebrán, Jorge; Garzón-Lasso, Fernando (Frontiers in Psychology, 2022)
The purpose of this study is to determine the effect of teleworking on self-reported job satisfaction and workers’ productivity in the context of the COVID-19 pandemic. A survey was administered to 331 teleworkers belonging to industrial companies, whose data were analyzed with a PLS-SEM structural equation model. The results indicate that communication with coworkers, time spent teleworking, and workplace suitability positively affect self-reported productivity, while trust on the part of supervisors and workplace suitability positively affect job satisfaction. On the other hand, work-family conflict negatively affects job satisfaction and self-reported productivity, whereas communication with coworkers, support from supervisor and time spent teleworking have no significant effect on job satisfaction. This study provides relevant information for industrial organizations to improve the job-satisfaction and productivity in large scaled teleworking contexts, as should have been implemented during the mandatory preventive isolation due to the health crisis related to the transmission of SARs-CoV-2.